Indonesian Version of Blended Learning Satisfaction Scale: A Translation, Validation, and Reliability Study - Lumbantoruan, Septa Meriana; Pangemanan, Alice Yvonne Yovita; Bureni, Abialbon Maharai; Hicha, Elvinazune Lisfareva; Sabatani, Elina Dewi (Universitas Airlangga, 2025)
Introduction: Since COVID-19 2019 became a global pandemic, the blended learning method has gained popularity, including in nursing education. A valid and trustworthy questionnaire is required in Indonesia to measure blended learning satisfaction. The purpose of this study was to evaluate the psychometric properties of Indonesian BLSS, a validated tool from Taiwan, among nursing students. Methods: This study employed a cross-sectional design to assess the validity and reliability of BLSS. The sample included 231 first-year nursing students from a university in Indonesia. The splitting sample method was utilized for exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The BLSS was translated using forward and backward translation. Three experts validated the content, while EFA and CFA investigated the structural validity. Reliability was assessed using Cronbach’s alpha. Results: The content validity index (CVI) of BLSS was 0.975. The mean age of the respondents was 19.26 (0.05), with the majority being female (85.07%). In EFA, one factor was retained based on cumulative variance, a scree plot, and parallel analysis. The CFA also showed one factor as retained. The factor loading of each item was greater than 0.5 both in EFA and CFA. This instrument has an internal consistency of 0.955 according to Cronbach’s alpha. Conclusion: The Indonesian BLSS is good, based on CVI, EFA, CFA and internal consistency analysis, which were used to measure satisfaction with blended learning. By measuring satisfaction following blended learning using BLSS, we hope that the learning process can be regarded as satisfactory and improved among nursing students.